Integration of Pancasila Student Profile with Civic Disposition: Building Character for Democratic Citizenship - Mazid, Sukron; Komalasari, Kokom; Abdulkarim, Aim; Rahmat, Rahmat; Abqa, Muhammad Ardhi Razaq; Wulansari, Atsani (JED (Jurnal Etika Demokrasi), 2024)
Education in Indonesia plays a vital role in shaping students' character based on Pancasila values. This study examines the integration of the Pancasila Student Profile with civic disposition to nurture character-driven citizens. Civic disposition encompasses attitudes and behaviors of responsible, independent, disciplined, polite, and tolerant individuals. Motivated by the need for character education rooted in Pancasila values, this research aims to analyze how such integration supports character development. Using qualitative methods, including descriptive analysis and interviews, the study explores educational strategies that internalize Pancasila values and civic disposition in learning. The findings reveal that this integration enhances students' awareness, responsibility, active participation, and character as citizens. Furthermore, it strengthens their resilience in addressing global challenges.  In conclusion, integrating Pancasila values with civic disposition effectively develops ethical, responsible, and high-integrity citizens.